Clinical research of the restoration efficacy in tunnel preparation restored with cermet glass-ionomer cements - Popović Milica O. (Serbian Medical Society - Dental Section, Belgrade, 2005)
The aim of this study was to evaluate clinical efficacy of tunnel restorations over 18-month observational period. Methods and material: Preparations were restored with glass-cermet-ionomer cement (Ketac-silver, DMG, Scandinavien AB). A total of 90 restorations were placed in 72 patients with age range 21-54 years old. Evaluation was carried out by clinical and radiographical means. Modified Cvar and Ryge criteria were used for evaluation j of marginal adaptation, marginal discoloration, surface structure, secondary caries and marginal ridge. Results: Fracture of marginal ridge was recorded in 4,7% of the restorations. No secondary aries or marginal discoloration were recorded. Conclusion: The results indicate that tunnel glass cermet ionomer cement restorations are useful in small proximal dentine lesions in permanent teeth. .